2018
DOI: 10.1111/1475-4932.12439
|View full text |Cite
|
Sign up to set email alerts
|

Asia's Third Giant: A Survey of the Indonesian Economy

Abstract: This paper surveys the Indonesian economy and the drivers of socioeconomic development over the past half‐century. It highlights the country's rapid economic development in the face of unfavourable ‘initial conditions’. We examine episodes in economic development, in particular comparing and contrasting the two main sub‐periods, of high economic growth during the authoritarian Suharto era, 1966–98, and moderate economic growth during the democratic era since 1999. The paper emphasises the importance of sound m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…It might be conjectured that poverty would be less responsive to growth during the authoritarian, centralized Soeharto regime compared to the democratic regime after 1999, which also saw the introduction of modest social welfare transfers. Yet, summarizing this literature, I have argued elsewhere that many of the Soeharto era policies were actually pro-poor (Hill 2000(Hill , 2018. Moreover, political theory informs us that there is no guarantee under democracy that the voting preferences of the majority would necessarily attach a high weight to the welfare of the bottom 10%-20% of the population in terms of income distribution.…”
Section: Cmentioning
confidence: 99%
“…It might be conjectured that poverty would be less responsive to growth during the authoritarian, centralized Soeharto regime compared to the democratic regime after 1999, which also saw the introduction of modest social welfare transfers. Yet, summarizing this literature, I have argued elsewhere that many of the Soeharto era policies were actually pro-poor (Hill 2000(Hill , 2018. Moreover, political theory informs us that there is no guarantee under democracy that the voting preferences of the majority would necessarily attach a high weight to the welfare of the bottom 10%-20% of the population in terms of income distribution.…”
Section: Cmentioning
confidence: 99%
“…If high redundancy costs restrict FDI, they may reduce worker productivity and thus long-run living standards. Hill ( 2018 ) also noted that onerous severance pay requirements in Indonesia reduce formal sector employment growth and increase dualism between wealthier formal sector workers and poorer informal sector workers.…”
Section: Increasing Manufacturing Exportsmentioning
confidence: 99%
“…Yoshitomi ( 2003 ) noted that entrepreneurs and workers learned new ways of organizing economic activity and acquired new skills. Hill ( 2018 ) reported that productivity and wages in Indonesia grew rapidly after it embraced a labor-intensive, export-oriented industrialization strategy.…”
Section: Increasing Manufacturing Exportsmentioning
confidence: 99%
“…The contribution of MSMEs to the Indonesian economy includes the ability to absorb 97% of the total workforce and can collect up to 60.4% of the total investment. However, the high number of MSMEs in Indonesia is also inseparable from the existing challenges (Hill, 2018). To answer this challenge, the government has implemented a number of MSME support programs, including incentive and financing assistance through the PEN program, People's Business Credit, the Proudly Made in Indonesia National Movement (Lin, 2018), Digitalization of MSME marketing, strengthening alumni entrepreneurs of the Pre-Employment Card Program through KUR Financing, and including a long-term strategy to raise the MSME class through the Job Creation Law (Gunawan, M., Asyahira, R., & M Sidjabat, 2020).…”
Section: Introductionmentioning
confidence: 99%